2021
DOI: 10.3390/jcdd8060068
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Immunosuppression Medications among Heart Transplant Recipients: Challenges, Opportunities, and Potential Role of Digital Approaches in the COVID-19 Era

Abstract: Society and medical practice have been restructured dramatically to avoid further spread of the COVID-19 virus; telehealth/telemedicine, mask wearing, and nationwide social distancing practices have become widespread. However, we still face unprecedented challenges in fields where patients require frequent and active follow-up visits for monitoring, including that of solid-organ transplant, and in particular, heart transplant. Adherence to immunosuppression remains a unique challenge in heart transplantation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Some other cohort studies towards solid organ transplant recipients showed a similar conclusion: almost no patients completely discontinued the use immunosuppressants, but other nonadherence behaviors, such as delayed doses or skipping a dose, were very commonly seen in COVID-19 era. 8,9 We can find similar phenomena in rheumatic diseases population. According to a survey conducted in America in April 2020, 48% of even not obtain the drugs they need totally.…”
Section: Discussionsupporting
confidence: 59%
“…Some other cohort studies towards solid organ transplant recipients showed a similar conclusion: almost no patients completely discontinued the use immunosuppressants, but other nonadherence behaviors, such as delayed doses or skipping a dose, were very commonly seen in COVID-19 era. 8,9 We can find similar phenomena in rheumatic diseases population. According to a survey conducted in America in April 2020, 48% of even not obtain the drugs they need totally.…”
Section: Discussionsupporting
confidence: 59%
“…This aspect should be considered a fundamental component of telemedicine practices for this patient cohort. Additionally, some researchers have directed their attention to the utilization of mobile health (m-Health) to bolster post-transplantation self-management for patients and enhance medication adherence [99,100]. The mHeart study [101] investigated the use of the mHeart mobile application and demonstrated a notable rise in drug adherence compared to standard care, along with a notable improvement in patients' perceived ease and understanding of medication regimens.…”
Section: Telehealth In Left Ventricular Assist Device and Heart-trans...mentioning
confidence: 99%
“…Aziz et al [5] note that the effect of this shift in the care of transplant patients is currently unknown but may affect short and long-term patient outcomes. Similar to medical professionals’ changing duties, in the initial stages of the pandemic, many adult and pediatric patients may have experienced a disruption to their work or school schedules [6 ▪▪ ]. Many schools transitioned to virtual learning and some businesses transitioned to a ‘work-from-home’ model.…”
Section: Severe Acute Respiratory Syndrome Corona Virus Disease Of 20...mentioning
confidence: 99%